2014
DOI: 10.1177/1470320314540733
|View full text |Cite
|
Sign up to set email alerts
|

The D allele of angiotensin-converting enzyme gene is associated with greater hemodynamic response to resistance exercises

Abstract: Hypothesis/introduction: The association of ACE I/D polymorphism and hemodynamic response to exercise have been limited to primarily aerobic exercises. We hypothesized that D allele carriers would show greater hemodynamic response to resistance exercise, as has been observed with aerobic. This study aimed to investigate the association of ACE I/D polymorphism and hemodynamic (blood pressure (BP), heart rate (HR) and rate-pressure product (RPP)) response to resistance exercise in young healthy subjects. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…The ACE D allele has been associated with greater muscle power phenotypes after resistance exercise (Erskine et al, 2014; Freire et al, 2015). In our study the muscle damage markers measured before the race and CK and LDH levels measured immediately after the race were also lower in DD homozygotes, similar to results previously reported (Amir et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The ACE D allele has been associated with greater muscle power phenotypes after resistance exercise (Erskine et al, 2014; Freire et al, 2015). In our study the muscle damage markers measured before the race and CK and LDH levels measured immediately after the race were also lower in DD homozygotes, similar to results previously reported (Amir et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with Freire et al (2015) who adopted 50%, 75%, and 100%10 RM strength exercises. Their results showed that the DD genotype had a significantly greater SBP incremental response immediately after each exercise than the II or ID genotype [ 37 ]. This result may be attributed to the higher concentration of ACE in the DD genotype and the release of ACE by exercise stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…At present, few studies have explored the effects of ACE on PEH. Previous studies have shown that there was different blood pressure altered in the people with different ACE genes after exercise [ 34 , 37 , 38 ]. Freire et al (2015) found that the SBP of people with the DD genotype at a resting state was significantly higher than those with the II or ID genotype [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations